2013
DOI: 10.1037/prj0000026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative impact of professional mental health background on ratings of consumer outcome and fidelity in an illness management and recovery program.

Abstract: The results demonstrate that IMR can be implemented with good fidelity and generate positive outcomes when delivered by practitioners who receive sufficient training and supervision regardless of their professional background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The most widely researched of the five programs is IMR (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Like WRAP, several studies included researchers who were also involved in the development of the program.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The most widely researched of the five programs is IMR (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Like WRAP, several studies included researchers who were also involved in the development of the program.…”
Section: Empirical Evidencementioning
confidence: 99%
“…The major quasi-experimental study occurred in Israel (38). Only IMR scales were used, and two of the 15 items were excluded, along with the associated module covering drug and alcohol use.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Our first secondary feasibility criterion was that the institute could achieve total scores on the IMR Fidelity Scale of ≥ 4.0, which is considered to reflect good fidelity [51, 55]; in other earlier research on IMR, cut-off scores for good or high IMR fidelity were > 3.7 [6], > 3.8 [56]. In their review, McGuire et al reported a weighted mean of 4.05 on fidelity for “all studies” (SD = .93) [5].…”
Section: Methodsmentioning
confidence: 99%
“…We included studies that investigated the efficacy of a psychosocial (i.e., non-medicationbased) intervention delivered by a non-licensed paraprofessional via coaching [34]. Across studies, equivalent, and at times superior, outcomes have been reported for paraprofessional-delivered interventions when compared to professionally led treatments [35][36][37][38]. Despite these promising findings, given the variability in the characteristics and severity of illnesses investigated, it is important not to assume that paraprofessional-delivered interventions will be as promising when applied to PTSD populations.…”
Section: Step 3: Selecting the Studiesmentioning
confidence: 99%